2012
DOI: 10.2147/ppa.s34345
|View full text |Cite
|
Sign up to set email alerts
|

Short-term clinical stability and lack of insight are associated with a negative attitude towards antipsychotic treatment at discharge in patients with schizophrenia and bipolar disorder

Abstract: PurposeThe primary aim of this study was to assess the range of attitudes towards antipsychotic treatment at hospital discharge in patients with schizophrenia and bipolar disorder. The secondary aim was to analyze the relationship between patients’ attitudes and sociodemographic and clinical parameters.Patients and methodsA cross-sectional study with a sample of patients admitted due to acute exacerbation of schizophrenia or a manic episode was conducted. Attitude towards pharmacological treatment at discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
3
22
1
Order By: Relevance
“…Then, they assessed a mean DAI score of 4.92 for adherent patients, which is comparable to the score measured in our study (4.79 at follow-up). An observational study by Medina et al reported a mean DAI score of 2.1 at discharge in patients with schizophrenia and bipolar patients [ 42 ], which corresponds to the DAI score of control patients (2.12) in our trial. Even though a high percentage achieved a DAI score > 0, the absolute scores of (non-) adherent patients remain rather low, between 2 and 5.…”
Section: Discussionsupporting
confidence: 56%
“…Then, they assessed a mean DAI score of 4.92 for adherent patients, which is comparable to the score measured in our study (4.79 at follow-up). An observational study by Medina et al reported a mean DAI score of 2.1 at discharge in patients with schizophrenia and bipolar patients [ 42 ], which corresponds to the DAI score of control patients (2.12) in our trial. Even though a high percentage achieved a DAI score > 0, the absolute scores of (non-) adherent patients remain rather low, between 2 and 5.…”
Section: Discussionsupporting
confidence: 56%
“…Aki et al [18] suggested that the patient's QOL could be predicted by the life skills measured by a family member and suggested that active treatment for depressive and negative symptoms might be recommended to improve the patient's QOL and life skills. An earlier study [19] also supports the value of patients' attitudes towards antipsychotic treatment at hospital discharge. Therefore, patient education is important in order to provide appropriate information to the patient, and patients' better understanding about basic information of their illness and treatments, including not only pharmacological treatments but also psychosocial approach to mental health, at the time of the first medical examination.…”
Section: Discussionmentioning
confidence: 53%
“…Our results are consistent with previous studies that have analysed the relationship between these variables. For example, a cross-sectional study of patients with schizophrenia or bipolar disorder admitted due to acute exacerbation of their condition found that insight was related to patient attitude towards antipsychotic treatment at hospital discharge [ 24 ]. Another cross-sectional study with 38 inpatients who met ICD-10 criteria for schizophrenia or schizoaffective disorder showed that therapeutic alliance was significantly correlated with adherence and that a weak therapeutic alliance and low insight were associated with poor adherence [ 13 ].…”
Section: Discussionmentioning
confidence: 99%